2019
DOI: 10.1186/s12888-019-2219-z
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of resilience and self-esteem between negative life events and positive social adjustment among left-behind adolescents in China: a cross-sectional study

Abstract: Background In China, adolescents are frequently left behind by their parents. A great deal of scientific evidence demonstrates considerable psychological and social impacts that negative life events may have on adolescents who are left behind. While a direct relationship between negative life events and psychological and social effects has been observed, indirect effects have yet to be examined. Therefore, the objective of this study was to determine the association between negative life events an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 56 publications
2
38
0
1
Order By: Relevance
“…Some research results are consistent with our conclusions. Two study found a signi cant correlation between the positive coping strategies of such children and their own mental health [17,38]. Zhao and colleagues concluded that the experience of being left behind made these children use more negative coping strategies to deal with di culties, which could result in mental health problems [40].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some research results are consistent with our conclusions. Two study found a signi cant correlation between the positive coping strategies of such children and their own mental health [17,38]. Zhao and colleagues concluded that the experience of being left behind made these children use more negative coping strategies to deal with di culties, which could result in mental health problems [40].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous empirical studies have shown that social support signi cantly related to one's level of selfesteem [17,18]. Social support is a broad concept, which in a broad sense refers to instrumental assistance (such as helping with work), emotional assistance (such as providing encouragement) or informational assistance (such as informing someone that there is a job opportunity) from others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, Zeigler-Hill & Wallace, (2012) also proven linked between self-esteem and adjustment problems. Social adjustment may also hinder the self-esteem in adolescents (Gao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…These may resultant in lowering the adjustment level (Zeigler-Hill & Wallace, 2012). Another study established the fact that social adjustment can be directly affected by the self-esteem in adolescents (Gao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%